2020
DOI: 10.17860/mersinefd.750957
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Learning Activities Based on 5E Learning Model on 4thGrade Science Teaching

Abstract: This study aims to investigate the effects of the 5E learning model on students' academic achievement, basic process skills, attitude towards science, and the overcoming of misconceptions. The study was carried out by means of semi-experimental research design. The participants consisted of 41 fourth grade students. They were randomly selected and assigned to the control and the experimental groups. The activities in the force and motion and the properties of matter topics in the fourth grade science curriculu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The reason for this finding of the research is that "the depth of the acquisitions contained in the units in terms of knowledge and cognitive processes and their compatibility with the teaching method-strategy" used. As a matter of fact, the reason presented by the studies included in the research Eyecioğlu & Yeşilyurt 2021;Demir and Emre, 2020; is also in this direction. In the research, a tendency towards the use of "Teaching Methods Based on Argumentation, Research, Inquiry and Scientific Process Skills, and Laboratory and Experiment Centered Teaching Methods" has been identified.…”
Section: Discussionmentioning
confidence: 98%
“…The reason for this finding of the research is that "the depth of the acquisitions contained in the units in terms of knowledge and cognitive processes and their compatibility with the teaching method-strategy" used. As a matter of fact, the reason presented by the studies included in the research Eyecioğlu & Yeşilyurt 2021;Demir and Emre, 2020; is also in this direction. In the research, a tendency towards the use of "Teaching Methods Based on Argumentation, Research, Inquiry and Scientific Process Skills, and Laboratory and Experiment Centered Teaching Methods" has been identified.…”
Section: Discussionmentioning
confidence: 98%
“…The outcomes of the investigation showed advancement in students' understanding and performance in the posttest results. The academic achievement, process skill, and attitude of the 4 th grade students toward the science learning using the 5E Instructional Model were evaluated by (DEMİR & İrfan, 2020). The study reported positive coreelation between students' performance and the application of the 5E model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, several studies in the literature stated that the 5E learning model enhanced learning motivation in science classes (Guven et al, 2022;Putra et al, 2018;Rizki et al, 2023). Studies have also demonstrated that the 5E learning model, as an application of constructivist learning theory, positively affects students' motivation, attitude, and success (Demir & Emre, 2020;Putra et al, 2018;Yalcin Altun et al, 2010). In this context, recent studies have also explored the use of the 5E learning model in conjunction with different techniques, methods, and strategies (Bagci & Yalin, 2018;Koc & Sarikaya, 2020;Utami & Subali, 2020).…”
Section: Introductionmentioning
confidence: 99%